A review of the design, properties, applications, and prospects of Ni-based composite powders. (October 2021) - Feng, Yuan; Yang, Haitao; Yang, Zekun; Hu, Chaoquan; Wu, Congcong; Wu, Lirong
Graphic abstract: Highlights: Synthesis strategies and mechanisms of Ni-based composite powder are evaluated. Properties and applications of Ni-based composite powder are summarized. Recent progress and significant findings of Ni-based composite powder are reviewed. Current challenges and future directions of Ni-based composite powder are discussed. Abstract: Ni-based composite powder (NCP) has attracted increasing attention due to its unique advantages. Various NCPs have been synthesized successfully by different raw powders, and synthesis strategies and applications of NCP have been designed. However, the mechanism of Ni coating is still in the early stage, and timely updates of recent research progress on new remarkable breakthroughs in NCP are highly desired. In light of the above, the novel synthesis designs and mechanism of NCP were discussed in this review. In addition, this review focused on the application of NCP in electrocatalysis, functional coating, and energy field. The future directions of various NCPs were summarized. Some innovative suggestions were discussed at the end of the article.